Novel human multiple myeloma cell line UHKT-893 - Uherková, Lenka; Vančurová, Irena; Vyhlídalová, Ilona; Pleschnerová, Markéta; Spička, Ivan; Mihalová, Romana; Březinová, Jana; Hodný, Zdeněk; Cermáková, Kamila; Polanská, Veronika; Marinov, Iuri; Jedelský, Petr L; et al. (Leukemia research, 2013)
We established and characterized a new IL-6 dependent multiple myeloma (MM) cell line UHKT-893 from the bone marrow of a relapsed 57-year-old woman. RESULTS: Using nephelometry, cells with plasma cell phenotype and morphology were found to secrete IgG and free kappa (κ)-light chain of immunoglobulin. κ-Light chain was also recognized intracellularly by flow cytometry and by mass spectrometry. VH4-39 region of IgVH genes was rearranged and somatically hypermutated. Cytogenetic analysis of cells revealed new chromosome abnormalities in all breakpoints unique in both MM patients and cell lines - t(1;6), t(1;11), t(5;15), t(5;21), +der(11;15) and der(16). IL-6 independent subline UHKT-893a was established by adaptation to descending IL-6 concentration, while the original cell line keeps on maintaining its IL-6 dependency. CONCLUSION: The cell line provides a suitable material for cellular and molecular studies of tumor abnormalities, with potentially unique mutagenic features of myeloma disease. It may be utilized for human hybridoma construction and vaccine development. Both IL-6 dependent and independent cell clones represent an important model for studies of myeloma cell growth and resistance emerging during targeted therapy.
Keywords: proliferace buněk; primární buněčná kultura; Recurrence; Female; Cell Line, Tumor; ženské pohlaví; cytogenetické vyšetření; buňky kostní dřeně; lidé; mnohočetný myelom; recidiva; Cytogenetic Analysis; Interleukin-6; Bone Marrow Cells; interleukin-6; Cell Proliferation; Primary Cell Culture; lidé středního věku; Multiple Myeloma; Middle Aged; nádorové buněčné linie; Humans